Semi-fragile tamper detection in image watermarking for checking the image integrity - Ernawan, Ferda; Amrullah, Agit; Gunawan, Teddy Surya; Nor Bakiah, Abd. Warif; Syifak Izhar, Hisham (IEEE, 2025)
Modern information technology enables users to exchange potentially manipulated digital images. This research introduces a tamper detection scheme in image watermarking to verify image authenticity. The research employs a two-stage integer wavelet transform (IWT), generating authentication bits through a bitwise XOR operation between approximation coefficients and a random binary matrix. The authentication data are strategically inserted into horizontal and vertical subbands. By cross-referencing these authentication bits, the method can detect image tampering. Experimental results demonstrate the approach’s effectiveness in identifying both intentional and unintentional image modifications. The technique achieved a peak signal-to-noise ratio (PSNR) of 54 dB and a structural similarity index (SSIM) of 0.9987 for watermarked images. The proposed method showed remarkable performance in tamper detection, with an average accuracy of 0.97 across various attack scenarios. The scheme successfully detected over 0.97 accuracy in challenging scenarios like collage, copy-paste, and object deletion attacks.